2018
DOI: 10.1177/0954008318778894
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the thermal ageing process and mechanism of benzoxazine/bismaleimide/cyanate ester copolymer

Abstract: Fibre-reinforced polymer (FRP) composites with thermosetting resin matrices are widely used in civil engineering (e.g. pultruded FRP plates and bars), and their thermal ageing behaviour is a concern when they are subjected to elevated temperatures (e.g. FRP chimney). In the present article, the effects of thermal ageing at 200°C and 250°C in air for up to 1000 h on mechanical properties and mechanism of the benzoxazine (Boz), bisphenol A dicyanate cyanate ester (BADCy), and 4,4′-bismaleimidodiphenyl methane (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Using the artificial accelerated thermal-oxidative aging test method according to the T g of the unaged specimens, determined as described in “Dynamic mechanical analysis” section, 27,28 thermal-oxidative aging was conducted in a DHG-9140A electrothermal constant temperature blast drying oven (Shanghai Linpin Instrument Stock Co., Ltd, Shanghai, China) at 190°C for 40 days. The change in mass was determined by weighing every day with the ALC-210.4 analytical balance of Sartorius Scientific Instruments Co., Ltd (Beijing, China), and the mass-loss rate was then calculated by…”
Section: Methodsmentioning
confidence: 99%
“…Using the artificial accelerated thermal-oxidative aging test method according to the T g of the unaged specimens, determined as described in “Dynamic mechanical analysis” section, 27,28 thermal-oxidative aging was conducted in a DHG-9140A electrothermal constant temperature blast drying oven (Shanghai Linpin Instrument Stock Co., Ltd, Shanghai, China) at 190°C for 40 days. The change in mass was determined by weighing every day with the ALC-210.4 analytical balance of Sartorius Scientific Instruments Co., Ltd (Beijing, China), and the mass-loss rate was then calculated by…”
Section: Methodsmentioning
confidence: 99%
“…The substrate was oxidized to produce chemical ageing, and a large number of cracks were generated at the interface between the fibre and the matrix. 25 Oxygen entered the interior of the material through these cracks, which increased the contact area and accelerated the rate of thermal-oxidative ageing. 26…”
Section: Resultsmentioning
confidence: 99%
“…23,28 At the aging temperature of 190°C, the interfacial debonding deteriorates with increasing aging time, voids appear between the fibers and matrix, and matrix cracking becomes extensive. 18,22,23 This may be because aging at 190°C has little effect on the fibers but leads to the matrix shrinkage; the variation of thermal expansion coefficients leads to shrinkage stress and interfacial damage. 29,30…”
Section: Resultsmentioning
confidence: 99%
“…The properties of composites subjected to thermal–oxidative aging have been studied extensively. Wang et al 18 investigated the properties of the benzoxazine/bismaleimide/cyanate ester copolymer subjected to thermal aging at 200°C and 250°C for 1000 h. They found that thermal oxidation and surface microcrack formation were the main results of thermal aging. Akay et al 19 studied the thermal aging of carbon fiber composites for 2000 h at temperatures of 210°C, 230°C, and 250°C.…”
Section: Introductionmentioning
confidence: 99%